The Role of the Internet in Women's Empowerment in Afghanistan: A Case Study of Online Universities - Hassani, Zahra; Nakisa Alizaey; Sabrina Karimi; Maryam Khalili; Ahmadi, Lima; Tamana Asghari (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2025)
This study explores the role of online universities in empowering women in Afghanistan, particularly focusing on the challenges and opportunities associated with digital education. Afghanistan, with its unique socio-political landscape, presents significant barriers to women's access to education, making online education a viable alternative. The purpose of this research is to assess the impact of online education on Afghan women's empowerment by examining their access to education, professional development, and digital literacy. A self-administered questionnaire was distributed to 150 female students from four faculties—Computer Science, Education, Economics, and Medicine—at an online university. The data were analyzed to determine the extent of online education’s contribution to empowering women in Afghanistan. Results indicate that online education has provided significant opportunities for professional development, though challenges such as limited internet access and digital literacy gaps remain. The study concludes that while online education plays a transformative role in empowering Afghan women, there is a critical need for improved internet infrastructure and digital literacy programs to maximize its impact.